Empowering Teens to?Make?a?Difference?in?Their?At-Risk?Community - Lisa Rothenburger; Alayne Torretta ([TEST] Journal of Extension, 2021)
When identifying problems and creating solutions that support the community?culture of health, youths?provide a unique perspective.?This article describes how staff from Somerset County, NJ 4-H?partnered?with staff from Middle Earth, an at-risk youth service provider, to organize a?group of?teens?who identified and implemented projects?that affect the health and wellness of their community of Bound Brook, NJ.? Extension professionals can replicate a sustainable and synergistic youth-adult partnership by creating the opportunities, making the initial connections within the community, and following the 4-H club model to ensure teens experience the essential elements.
Keywords: youth/adult partnership; community development; youth organizing; leadership; Citizenship